Diversidade genética e mapeamento por associação em linhagens de milho para maturação de grãos - Friske, Élcio (2016)
The aim of this work was to evaluate the genetic diversity and map genomic regions associated with grains maturation in common corn lineages. The phenotypic attributes of 81 elite inbred lines of corn were assessed in field experiment implanted in square lattice design with three repetitions. The variance and multivariate analysis were carried out considering complete randomized blocks due to its equivalence with the estimation for the lattice efficiency. For the mapping by linkage disequilibrium, 72 elite inbred lines have been genotyped for SNP markers at platform 650K (Affymetrix®) and associated with the genotypic values of the traits related to maturation: number of days for the male flowering (DFM) and female (DFF), and the grain moisture loss, determined by the area below the moisture curve (AACUM). The results of the variance analysis pointed out the existence of genetic diversity in the germplasm for all the assessed traits, detecting a wide variability for DFM, DFF and AACUM. Weak genetic correlations between yield and maturation components indicated the possibility of selection for earliness without compromising the grain yield. The genetic diversity quantified by the distances of Mahalanobis enabled the suggestion of hybrid combinations of higher heterotic effect for earliness and grain yield. There were similarities in the Tocher and UPGMA grouping, which were efficient to classify the genetic variability. By the mixed linear model (MLM) it was possible to detect associations among days for male and female flourishing with SNP markers in all chromosomes, with predominance of chromosomes 1 and 3 and for the loss of moisture in the chromosomes 5 and 6. With of multiple regression analysis of stepwise for DFM, DFF and AACUM, the complete models explained 79%, 93% and 56% of the variation for the genotypic values, respectively, being found predominantly significant markers in the chromosomes 1 and 3. The detection of similar and also different genomic regions for these traits, which are highly correlated, makes possible to raise the hypothesis of the importance of the genetic linkage and pleiotropy to explain the maturation of grains in corn inbred lines. The results obtained are promising and the genomic regions associated with DFM, DFF and AACUM, will be evaluated in validation experiments, which will be useful in selection programs of genotypes with the maturity sought by the breeder